A Reliable Analytical Method for Solving Higher-Order Initial Value Problems. (2nd December 2013) - Abu Arqub, Omar; Abo-Hammour, Zaer; Al-Badarneh, Ramzi; Momani, Shaher
Abstract : In this article, a new analytical method has been devised to solve higher-order initial value problems for ordinary differential equations. This method was implemented to construct a series solution for higher-order initial value problems in the form of a rapidly convergent series with easily computable components using symbolic computation software. The proposed method is based on the Taylor series expansion which constructs an analytical solution in the form of a polynomial and reproduces the exact solution when the solution is polynomial. This technique is applied to a few test examples to illustrate the accuracy, efficiency, and applicability of the method. The results reveal that the method is very effective, straightforward, and simple.